Combinatorial number theory : proceedings of the 'Integers Conference 2007', Carrollton, Georgia, USA, October 24-27, 2007 - Landman, Bruce; Nathanson, Melvyn Bernard; Nowakowski, Richard J.; Nešetřil, Jaroslav; Pomerance, Carl; Robertson, Aaron (De Gruyter Proceedings in Mathematics, 2009)
This volume contains selected refereed papers based on lectures presented at the 'Integers Conference 2007', an international conference in combinatorial number theory that was held in Carrollton, Georgia in October 2007. The proceedings include contributions from many distinguished speakers, including George Andrews, Neil Hindman, Florian Luca, Carl Pomerance, Ken Ono and Igor E. Shparlinski. Among the topics considered in these papers are additive number theory, multiplicative number theory, sequences, elementary number theory, theory of partitions, and Ramsey theory.